Corporate Social Responsibility as a Mediating Variable: The Impact of Environmental Performance, Firm Size, and Environmental Costs on Financial Performance of Manufacturing Companies Listed on the Indonesia Stock Exchange - Samosir, Yosafat Renovaldo; Simanjuntak, Arthur; Simanjuntak, Gracesiela; Simanjuntak, Wesly Andri (Basic and Applied Accounting Research Journal, 2025)
This study aims to analyze the role of Corporate Social Responsibility (CSR) as an intervening variable in the influence of environmental performance, company size, and environmental costs on financial performance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. The data used were obtained from annual reports and sustainability reports of companies published during the study period. The results of the study indicate that environmental performance, company size, and environmental costs have a significant effect on financial performance, both directly and indirectly through Corporate Social Responsibility (CSR) as an intervening variable. These findings indicate that Corporate Social Responsibility (CSR) has an important role in strengthening the relationship between a company's environmental factors and its financial performance. The results of the determination coefficient test show that 20.6% of the dependent variable (ROA) can be explained by the existing independent variables, namely financial performance, environmental costs, and company size, while the remaining 79.4% is influenced by other variables not explained in this study. The implications of this study indicate that companies need to integrate Corporate Social Responsibility (CSR) practices partially and mediating variables strategically to improve sustainability and long-term financial performance.